Electromagnetic wave shielding member and method for manufacturing the same

CN117397377BActive Publication Date: 2026-10-09DIC CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202280037295.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-05-25
Filing Date
2022-03-03
Publication Date
2026-10-09
Estimated Expiration
2042-03-03

AI Technical Summary

Technical Problem

然而,该方法中,也存在如下问题:PAS树脂成型品的表面被蚀刻液浸蚀而变得脆弱,形成于其上的镀铜层经时而容易被剥离

Benefits of technology

[0026] According to the present invention, an electromagnetic wave shielding component with excellent electromagnetic wave shielding properties formed by a laminate capable of forming a coating on the surface of a PAS resin molded article with high adhesive strength through a simpler process, and a method thereof can be provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004565503360000041
    Figure BDA0004565503360000041
  • Figure BDA0004565503360000042
    Figure BDA0004565503360000042
  • Figure BDA0004565503360000051
    Figure BDA0004565503360000051
Patent Text Reader

Abstract

Provided is a method for producing an electromagnetic wave shielding member having excellent electric field shielding property and magnetic field shielding property, which is formed of a laminate in which a plated layer is formed on the surface of a polyarylene sulfide (PAS) molded article with high adhesion by a simple process. Further in detail, for the electromagnetic wave shielding member and the method for producing the same, the method for producing an electromagnetic wave shielding member formed of a laminate, the method is characterized by comprising a step of roughening the surface of a molded article molded from a PAS resin composition by chemical etching treatment, and a step of plating the surface of the aforementioned molded article subjected to the roughening treatment, the aforementioned laminate being provided with a plated layer on at least two faces in pair, and the aforementioned PAS resin composition being compounded with a PAS resin (A), a thermoplastic resin (B) other than a polyarylene sulfide resin selected from the group consisting of a thermoplastic elastomer (b1) and a thermoplastic resin (b2) having hydrolysis property, a carbonate (C), and a polyolefin-based wax (D).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to electromagnetic wave shielding components and methods for manufacturing them. More specifically, it relates to electromagnetic wave shielding components formed by laminations capable of easily forming a coating on the surface of a molded article (hereinafter sometimes referred to as a polyarylether sulfide resin molded article) formed from a polyarylether sulfide resin composition with high adhesion, and methods for manufacturing the same. Background Technology

[0002] In recent years, the automotive industry has been actively pursuing various attempts to replace metal components with lighter, heat-resistant, and chemical-resistant engineering plastics to achieve fuel efficiency and other benefits through vehicle lightweighting. Among these, polyarylene sulfide (PAS) resins, represented by polyphenylene sulfide (PPS), are widely used due to their excellent heat resistance, mechanical strength, chemical resistance, processability, and dimensional stability.

[0003] On the other hand, with the electrification of automobiles, vehicles are equipped with numerous electronic control systems, raising concerns about the effects of electromagnetic waves generated from high-voltage components on the human body. For example, it is known that inverters, essential components of electric motors, generate low-frequency electromagnetic waves around 100kHz. Given this context, resin housings for various automotive components require not only the ability to shield against high-frequency electromagnetic waves, but also the ability to shield against low-frequency electromagnetic waves.

[0004] As an organic material, PAS resin has low electromagnetic wave shielding performance. Therefore, a method is usually adopted to form a thin film layer containing metal or ceramic on the surface of the resin molded article. However, due to the high chemical resistance of PAS resin, PAS resin compositions and PAS resin molded articles are difficult to bond (binder) with other materials. Therefore, even if a metal film is formed on its surface, there is a problem that the metal film is easy to peel off.

[0005] As a solution to the above problems, a method has been proposed as follows: the surface of the PAS resin molded article is etched with an etching solution, and then a palladium catalyst is applied before chemical copper plating to form a copper plating layer (see, for example, Patent Document 1). However, this method also has the following problems: the surface of the PAS resin molded article becomes brittle due to the etching solution, and the copper plating layer formed thereon is easily peeled off over time.

[0006] In addition, a method has been proposed to improve the adhesion to coatings such as metal vapor deposition and metal plating by roughening the surface of PAS resin molded parts through sandblasting, shot peening, etc. (see Patent Document 2). However, in order to ensure sufficient adhesion, the surface of polyphenylene sulfide is roughened to a depth of 1 to 10 μm, so it is not suitable for components that require a smooth surface.

[0007] In addition, a method has been proposed that involves forming a primer resin layer and a metal layer containing metal particles on the surface of a PAS resin molded article using an immersion method, followed by forming a metal plating layer using electrolytic plating, chemical plating, or other methods, wherein a metal film is formed on the surface of the polyphenylene sulfide (see Patent Documents 3 and 4). However, this method involves sequentially forming a primer resin layer, a metal layer containing metal particles, and a metal plating layer on the surface of the PAS resin molded article, thus involving a large number of steps. From a productivity perspective, it is desirable to propose a method with fewer steps.

[0008] Existing technical documents

[0009] Patent documents

[0010] Patent Document 1: Japanese Patent Application Publication No. 63-14880

[0011] Patent Document 2: Japanese Patent Application Publication No. 2002-97292

[0012] Patent Document 3: International Publication No. 2017 / 154879

[0013] Patent Document 4: Japanese Patent No. 6355008 Summary of the Invention

[0014] The problem the invention aims to solve

[0015] The problem to be solved by the present invention is to provide an electromagnetic wave shielding component with excellent electric field shielding and magnetic field shielding properties, formed by a laminate of which a coating can be formed on the surface of a PAS resin molded article with high adhesion in a simple process, and a method thereof.

[0016] Solution for solving the problem

[0017] In order to solve the above-mentioned problems, the inventors conducted in-depth research and found that: when a molded article made by melt molding a PAS resin composition consisting of a mixture of PAS resin (A), a thermoplastic resin (B) other than PAS resin selected from the group consisting of thermoplastic elastomer (b1) and hydrolyzable thermoplastic resin (b2), carbonate (C) and polyolefin wax (D) is roughened by chemical etching, the coating formed by plating on the roughened surface exhibits high adhesion. Furthermore, when plating is performed on at least two pairs of surfaces, the electric field shielding and magnetic field shielding are even better, thus completing the present invention.

[0018] That is, this disclosure relates to a method for manufacturing an electromagnetic wave shielding component, characterized in that it is a method for manufacturing an electromagnetic wave shielding component formed by a laminate, the manufacturing method comprising the following steps: a step of roughening the surface of a molded article formed from a PAS resin composition by chemical etching, and a step of plating the roughened surface of the aforementioned molded article.

[0019] The aforementioned laminate has a coating on at least two paired surfaces.

[0020] The aforementioned PAS resin composition is made by compounding PAS resin (A), thermoplastic resin (B) other than PAS resin selected from the group consisting of thermoplastic elastomer (b1) and hydrolyzable thermoplastic resin (b2), carbonate (C) and polyolefin wax (D).

[0021] Furthermore, this disclosure relates to an electromagnetic wave shielding component, characterized in that it is formed by laminating a coating onto the roughened surface of a molded article formed from a PAS resin composition.

[0022] The plating of the aforementioned laminate is present on at least two paired surfaces.

[0023] The aforementioned PAS resin composition is made by compounding PAS resin (A), thermoplastic resin (B) other than PAS resin selected from the group consisting of thermoplastic elastomer (b1) and hydrolyzable thermoplastic resin (b2), carbonate (C) and polyolefin wax (D).

[0024] It should be noted that in this disclosure, the bonding between the surface of the PAS resin molded article and the coating is referred to as adhesion or sealing.

[0025] The effects of the invention

[0026] According to the present invention, an electromagnetic wave shielding component with excellent electromagnetic wave shielding properties formed by a laminate capable of forming a coating on the surface of a PAS resin molded article with high adhesive strength through a simpler process, and a method thereof can be provided. Detailed Implementation

[0027] The method for manufacturing an electromagnetic wave shielding component disclosed herein is characterized in that it is a method for manufacturing an electromagnetic wave shielding component formed by a laminate, the method comprising the following steps: using a molded article formed from a PAS resin composition as a support, and roughening the surface of the support by chemical etching; and plating the roughened surface of the support.

[0028] The aforementioned laminate has a coating on at least two paired surfaces.

[0029] The aforementioned PAS resin composition is made by compounding PAS resin (A), thermoplastic resin (B) other than PAS resin selected from the group consisting of thermoplastic elastomer (b1) and hydrolyzable thermoplastic resin (b2), carbonate (C) and polyolefin wax (D).

[0030] <PAS Resin (A)>

[0031] The aforementioned PAS resin (A) has a resin structure in which an aromatic ring bonded to a sulfur atom is used as a repeating unit. Specifically, it is a resin in which the structural part shown in the following general formula (1) is used as a repeating unit.

[0032]

[0033] (where R is in the formula) 1 and R 2 Each of these groups independently represents a hydrogen atom, or an alkyl, nitro, amino, phenyl, methoxy, or ethoxy group having 1 to 4 carbon atoms.

[0034] For R in the above general formula (1) 1 and R 2 From the perspective of improving the mechanical strength of the aforementioned PAS resin (A), hydrogen atoms are preferred. In this case, examples of para-bonded ones shown in the following general formula (2) and meta-bonded ones shown in the following general formula (3) can be cited.

[0035]

[0036] In particular, when the sulfur atom in the repeating unit is bonded to the aromatic ring in the para-bonded structure shown in the above general formula (2), it is preferred from the perspective of improving the heat resistance and crystallinity of the aforementioned PAS resin (A).

[0037] Furthermore, the aforementioned PAS resin (A) may not only have the structural portion shown in the above general formula (1), but may also have at least one of the structural portions selected from those shown in general formulas (4) to (7) below. When the PAS resin (A) has the structural portions shown in general formulas (4) to (7) below, the molar ratio of these structural portions in the aforementioned PAS resin (A) is preferably 30 mol% or less, more preferably 10 mol% or less, from the viewpoint of improving heat resistance and mechanical strength.

[0038]

[0039] In the aforementioned PAS resin (A), if it contains the structural parts shown in the above general formulas (4) to (7), the bonding of the repeating unit with the structural part shown in the above general formula (1) can be random or block.

[0040] Furthermore, the aforementioned PAS resin (A) may also have 3 functional structural sites, naphthalene thioether bonds, etc., as shown in the following general formula (8) in its structure. It should be noted that, in this case, the molar ratio of these structural sites in the aforementioned PAS resin (A) is preferably 3 mol% or less, and more preferably 1 mol% or less.

[0041]

[0042] The aforementioned PAS resin (A) can be manufactured, for example, according to the methods described in (1) to (4) below.

[0043] (1) A method for reacting sodium sulfide with p-dichlorobenzene in amide solvents such as N-methylpyrrolidone, dimethylacetamide, or sulfone solvents such as sulfolane.

[0044] (2) A method for polymerizing p-dichlorobenzene in the presence of sulfur and sodium carbonate.

[0045] (3) A method of polymerization by adding sodium sulfide dropwise to a mixture of a polar solvent and p-dichlorobenzene, or by adding a mixture of sodium hydrosulfide and sodium hydroxide, or by adding a mixture of hydrogen sulfide and sodium hydroxide.

[0046] (4) A method based on the self-condensation of p-chlorothiophenol.

[0047] Of these methods, method (1), which involves reacting sodium sulfide with p-dichlorobenzene in amide solvents such as N-methylpyrrolidone, dimethylacetamide, or sulfone solvents such as sulfolane, is preferred due to its ease of reaction control and excellent industrial productivity. Furthermore, in method (1), to adjust the degree of polymerization, it is preferable to add alkalis such as alkali metal salts of carboxylic acids, alkali metal salts of sulfonic acids, or hydroxides.

[0048] The melt viscosity of the aforementioned PAS resin, measured at 300°C, is preferably 2 Pa·s or more, more preferably 10 Pa·s or more, further preferably 60 Pa·s or more to preferably 1000 Pa·s or less, more preferably 500 Pa·s or less, and further preferably 200 Pa·s or less. A melt viscosity of 2 Pa·s or more is preferred as it helps maintain material strength. Conversely, a melt viscosity of 1000 Pa·s or less is preferred from a moldability viewpoint. It should be noted that the value of "melt viscosity" used in this specification is the following: measured using a high-performance flow tester (Shimadzu Corporation, CFT-500D) at 300°C with a load of 1.96 × 10⁻⁶. 6 The value was obtained by measuring the melt viscosity (V6) after holding the product at Pa and L / D = 10 (mm) / 1 (mm) for 6 minutes.

[0049] Furthermore, regarding the aforementioned PAS resin (A), from the perspective of reducing the amount of residual metal ions, improving moisture resistance, and reducing the amount of residual low molecular weight impurities produced as a byproduct during polymerization, it is preferable to perform acid treatment after manufacturing the aforementioned PAS resin (A), followed by washing with water.

[0050] The acids used in the aforementioned acid treatment are preferably acetic acid, hydrochloric acid, sulfuric acid, phosphoric acid, silicic acid, carbonic acid, and propionic acid. Furthermore, among these acids, acetic acid and hydrochloric acid are preferred from the perspective of effectively reducing the amount of residual metal ions without decomposing the aforementioned PAS resin (A).

[0051] The aforementioned acid treatment method can be exemplified by impregnating the aforementioned PAS resin (A) with an acid or an aqueous acid solution. Further stirring or heating may be performed as needed.

[0052] Here, as a specific method of acid treatment, if we take the method of using acetic acid as an example, we can give the following method: First, heat the aqueous solution of acetic acid with pH 4 to 80-90°C, and impregnate the aforementioned PAS resin (A) in it, and stir for 20-40 minutes.

[0053] The aforementioned PAS resin (A) that has undergone acid treatment is then rinsed multiple times with water or warm water to physically remove residual acid and salt. Distilled water or deionized water is preferred for this purpose.

[0054] Furthermore, the PAS resin (A) supplied for the aforementioned acid treatment is preferably in powder or granule form, specifically, it can be a granular form like pellets or a polymerized slurry.

[0055] <Thermoplastic resins other than PAS resin (B)>

[0056] For the PAS resin molded articles of this disclosure, from the viewpoint of improving the adhesion to the coating obtained based on the aforementioned plating treatment, the PAS resin composition of the present invention further incorporates a thermoplastic resin (B) other than PAS resin as an essential component, selected from the group consisting of thermoplastic elastomer (b1) and hydrolyzable thermoplastic resin (b2).

[0057] The thermoplastic elastomer (b1) used in this disclosure is not particularly limited as long as it is a known material, and it is preferred to remove it by chemical etching, which will be described later. Specifically, examples include polyolefin-based thermoplastic elastomers (sometimes referred to as "olefin copolymer-based thermoplastic elastomers"), fluorinated thermoplastic elastomers, silicone-based thermoplastic elastomers, styrene-based thermoplastic elastomers, fluoropolymer-based thermoplastic elastomers, polyurethane resin-based thermoplastic elastomers, etc., with polyolefin-based thermoplastic elastomers being a particularly preferred example.

[0058] Examples of polyolefin-based thermoplastic elastomers include homopolymers of α-olefins, copolymers of two or more α-olefins, and copolymers of one or more α-olefins with vinyl polymerizable compounds having functional groups. Examples of α-olefins include ethylene, propylene, and 1-butene, which have 2 to 8 carbon atoms. Examples of functional groups include carboxyl groups, anhydride groups (-C(=O)OC(=O)-), epoxy groups, amino groups, hydroxyl groups, mercapto groups, isocyanate groups, and oxazoline groups. Furthermore, examples of the aforementioned vinyl polymerizable compounds with functional groups include vinyl acetate; α,β-unsaturated carboxylic acids such as (meth)acrylic acid; alkyl esters of α,β-unsaturated carboxylic acids such as methyl acrylate, ethyl acrylate, and butyl acrylate; metal salts of α,β-unsaturated carboxylic acids such as ionomers (as metals, alkali metals such as sodium, alkaline earth metals such as calcium, zinc, etc.); glycidyl esters of α,β-unsaturated carboxylic acids such as glycidyl methacrylate; α,β-unsaturated dicarboxylic acids such as maleic acid, fumaric acid, and itaconic acid; and one or more derivatives (monoesters, diesters, anhydrides) of the aforementioned α,β-unsaturated dicarboxylic acids. Additionally, examples include ethylene-propylene rubber (EPM), ethylene-propylene-diene rubber (EPDM), butadiene rubber, chloroprene rubber, nitrile rubber, butyl rubber, and acrylic rubber. In addition, examples of styrene-based thermoplastic elastomers include styrene-butadiene rubber (SBR) and hydrogenated SBR. Other examples include silicone-based thermoplastic elastomers such as silicone rubber, fluoropolymer-based thermoplastic elastomers such as fluoropolymer rubber, and polyurethane resin-based thermoplastic elastomers such as urethane rubber. These thermoplastic elastomers can be used alone or in combination of two or more.

[0059] As for the hydrolytic thermoplastic resin (b2), there is no particular limitation as long as it is a known hydrolytic thermoplastic resin, and resins that exhibit hydrolytic properties through the chemical etching treatment described later are preferred. Specifically, examples include polyamide resins, polyester resins, polycarbonate resins, polyether resins, polyurethane resins, polyketone resins, polylactone resins, polyacetal resins, polyimide resins, polyamide-imide resins, polyaryl ester resins, polyetherimide resins, polyetheretherketone resins, thermoplastic epoxy resins, thermoplastic phenolic resins, and copolymers containing the aforementioned resin structures.

[0060] Among the aforementioned thermoplastic resins (b2), polyamide resin and polycarbonate resin are preferred examples from the perspective of excellent adhesion between the obtained PAS resin molded article and the coating, and polyamide resin is a more preferred example.

[0061] As an example of the aforementioned aromatic polyamide resin, an aromatic polyamide resin comprising repeating units as shown in the following structural formula (10) can be cited.

[0062]

[0063] In the aforementioned structural formula (10), R 2 This refers to alkylene groups having 2 to 12 carbon atoms. Specifically, the aforementioned terephthalamide structure is formed by the reaction of terephthalic acid or terephthaloyl dihalides with an aliphatic diamine having 2 to 12 carbon atoms. Examples of aliphatic diamines having 2 to 12 carbon atoms include linear aliphatic alkylene diamines such as ethylenediamine, propylenediamine, 1,4-butanediamine, 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, and 1,12-dodecanediamine; and butyl-1,2-ethylenediamine, 1,1-dimethyl-1,4-butanediamine, 1-ethyl-1,4-butanediamine, etc. 1,2-Dimethyl-1,4-Butanediamine, 1,3-Dimethyl-1,4-Butanediamine, 1,4-Dimethyl-1,4-Butanediamine, 2,3-Dimethyl-1,4-Butanediamine, 2-Methyl-1,5-Pentanediamine, 3-Methyl-1,5-Pentanediamine, 2,5-Dimethyl-1,6-Hexanediamine, 2,4-Dimethyl-1,6-Hexanediamine, 3,3-Dimethyl-1,6-Hexanediamine, 2,2-Dimethyl-1,6-Hexanediamine, 2,2,4-Trimethyl-1,6- Hexamethylenediamine, 2,4,4-trimethyl-1,6-hexamethylenediamine, 2,4-diethyl-1,6-hexamethylenediamine, 2,2-dimethyl-1,7-heptanediamine, 2,3-dimethyl-1,7-heptanediamine, 2,4-dimethyl-1,7-heptanediamine, 2,5-dimethyl-1,7-heptanediamine, 2-methyl-1,8-octanediamine, 3-methyl-1,8-octanediamine, 4-methyl-1,8-octanediamine, 1,3-dimethyl-1,8-octanediamine, 1,4-dimethyl-1,8 - Branched aliphatic alkylene diamines such as octanediamine, 2,4-dimethyl-1,8-octanediamine, 3,4-dimethyl-1,8-octanediamine, 4,5-dimethyl-1,8-octanediamine, 2,2-dimethyl-1,8-octanediamine, 3,3-dimethyl-1,8-octanediamine, 4,4-dimethyl-1,8-octanediamine, and 5-methyl-1,9-nonanediamine; alicyclic diamines such as cyclohexanediamine, methylcyclohexanediamine, isophoronediamine, norbornenedimethylamine, and tricyclodecanedimethylamine.

[0064] Among these, linear aliphatic alkylene diamines with 4 to 8 carbon atoms and branched aliphatic alkylene diamines with 5 to 10 carbon atoms are particularly preferred, considering the superior adhesion between the resulting PAS resin molded product and the coating.

[0065] In addition, the aforementioned aromatic polyamide resin may also include an aromatic polyamide resin comprising repeating units as shown in the following structural formula (11).

[0066]

[0067] (where R is in the formula) 2 With R in structural formula (10) 2 (These have the same meaning.)

[0068] Furthermore, the aforementioned aromatic polyamide resin may also have an acid amide structure as shown in the following structural formula (12).

[0069]

[0070] (where R is in the formula) 2 With R in structural formula (10) 2 For the same meaning, R 3 (This refers to aliphatic hydrocarbon groups with 4 to 10 carbon atoms.)

[0071] Here, the acid amide structure shown in the above structural formula (12) is formed by the reaction of an aliphatic dicarboxylic acid with 4 to 10 carbon atoms, its esterified form, its anhydride, or its acyl halide with an aliphatic diamine with 2 to 12 carbon atoms. Specifically, examples of aliphatic dicarboxylic acids with 4 to 10 carbon atoms include malonic acid, dimethylmalonic acid, succinic acid, glutaric acid, adipic acid, 2-methyl adipic acid, trimethyl adipic acid, pimelic acid, 2,2-dimethylglutaric acid, 3,3-diethylsuccinic acid, azelaic acid, sebacic acid, octanoic acid, etc.; and alicyclic dicarboxylic acids such as 1,3-cyclopentanedicarboxylic acid and 1,4-cyclohexanedicarboxylic acid.

[0072] Specifically, examples of esters of aliphatic dicarboxylic acids with 4 to 10 carbon atoms include methyl esters, ethyl esters, and tert-butyl esters. Additionally, examples of halogen atoms constituting the aforementioned acyl halides of aliphatic dicarboxylic acids include bromine and chlorine atoms.

[0073] As described above, the aforementioned aromatic polyamide resin preferably has the amide structure shown in the aforementioned structural formulas (10), (11), and (12) as structural sites. When the acid amide structure composed of one molecule of dicarboxylic acid and one molecule of diamine is taken as a unit, it is preferable from the perspective that the adhesion of the obtained PAS resin molded article to the coating is better than that of the aforementioned terephthalic acid amide structure of 50 mol% or more, isophthalic acid amide structure of 10 mol% or more, and aliphatic hydrocarbon acid amide structure of 5 mol% or more, relative to all the acid amide structures constituting the aromatic polyamide resin.

[0074] Furthermore, regarding the aforementioned aromatic polyamide resin, from the perspective of superior adhesion between the obtained PAS resin molded article and the coating, the following is preferred:

[0075] Polyamide resins comprising the aforementioned terephthalamide structure shown in formula (10) in the range of 50 mol% to 80 mol% or more.

[0076] Polyamide resins comprising the isophthalamide structure shown in the aforementioned structural formula (11) in the range of 10 mol% to 30 mol% or less.

[0077] A polyamide resin comprising the acid amide structure shown in the aforementioned structural formula (12) in the range of 5 mol% to 20 mol%.

[0078] Furthermore, considering that the recrystallization peak temperature of the aforementioned aromatic polyamide resin becomes lower and the dispersibility with the aforementioned PAS resin becomes better, it is preferable that the melting point is in the range of 290°C or higher to 330°C or lower, and the glass transition temperature is in the range of 90°C or higher to 140°C or lower.

[0079] The aforementioned aromatic polyamide resin can be manufactured, for example, according to the methods described in (1) to (3) below.

[0080] (1) Interfacial polymerization method: After dissolving the acyl halide containing dicarboxylic acid of terephthalic acid and the diamine containing aliphatic diamine with 2 to 12 carbon atoms in two immiscible solvents, the two solutions are mixed and stirred in the presence of alkali and a quaternary ammonium salt of a catalyst amount, and a polycondensation reaction is carried out.

[0081] (2) Solution polymerization: An acyl halide containing dicarboxylic acid of terephthalic acid is reacted with a diamine containing an aliphatic diamine with 2 to 12 carbon atoms in an organic solvent in the presence of a basic compound that accepts an acid, such as a tertiary amine.

[0082] (3) Melt polymerization method: using esterified dicarboxylic acid containing terephthalic acid and aromatic diamine as raw materials, the amide exchange reaction is carried out in a molten state.

[0083] The mixing ratio of the aforementioned thermoplastic resin (B) is not particularly limited. From the perspective of further improving the adhesion to the coating obtained based on the aforementioned plating treatment, the total amount of thermoplastic resin (B) other than PAS resin in the group consisting of thermoplastic elastomer (b1) and hydrolyzable thermoplastic resin (b2) is preferably 5 parts by mass or more, more preferably 15 parts by mass or more, further preferably 30 parts by mass or more, and preferably 70 parts by mass or less, more preferably 60 parts by mass or less, and further preferably 50 parts by mass or less.

[0084] <Carbonates (C)>

[0085] For the PAS resin molded articles of this disclosure, from the perspective of improving the adhesion to the coating obtained based on the aforementioned plating treatment, the PAS resin composition of the present invention further incorporates a carbonate (C) as an essential component. As for this carbonate (C), there are no particular limitations as long as it is a known substance, and those that can be removed by the chemical etching treatment described later are preferred. Specifically, examples include calcium carbonate, magnesium carbonate, potassium carbonate, sodium carbonate, sodium bicarbonate, ammonium carbonate, barium carbonate, lithium carbonate, copper (II) carbonate, ferrous (II) carbonate, silver (I) carbonate, manganese carbonate, zinc carbonate, dolomite, and hydromagnesite, with calcium carbonate being a particularly preferred example.

[0086] The size of the aforementioned carbonate (C) is not particularly limited. However, from the perspective of achieving better adhesion between the obtained PAS resin molded article and the coating, its average particle size is preferably in the range of 6 μm or less, more preferably 3 μm or less, and even more preferably 1.2 μm or less. On the other hand, there is no limitation on the lower limit, but it is preferably in the range of 0.3 μm or more, more preferably 0.5 μm or more, and even more preferably 0.8 μm or more. It should be noted that, for this average particle size, the cross-section of the obtained molded article can be observed and photographed using an electron microscope. For example, a method can be used where at least 100 arbitrary particles are measured within an observation range of 3000 times the size of one side, and their average value is calculated.

[0087] The mixing ratio of the aforementioned carbonate (C) is not particularly limited. From the perspective of further improving the adhesion of the coating obtained based on the aforementioned plating treatment, the ratio is preferably 10 parts by mass or more, more preferably 25 parts by mass or more, more preferably 40 parts by mass or more, more preferably 90 parts by mass or less, more preferably 80 parts by mass or less, and more preferably 70 parts by mass or less, relative to 100 parts by mass of the aforementioned PAS resin (A).

[0088] <Polyolefin Wax (D)>

[0089] For the PAS resin molded articles of this disclosure, from the perspective of improving the adhesion to the coating obtained based on the aforementioned plating treatment, the PAS resin composition of the present invention is further blended with polyolefin wax (D) as an essential component.

[0090] The polyolefin wax used in this disclosure can be any known substance that has a polyolefin structure obtained by polymerizing monomers having an olefin structure. It should be noted that the wax in this invention refers to a low molecular weight resin, typically solid at 25°C, manufactured by polymerization, which exhibits a release effect in a mold when melt-molded as an additive to a PAS resin composition. Generally, this refers to a molecular weight (Mn) preferably in the range of 250 or more, more preferably 300 or more, and preferably 20,000 or less, more preferably 10,000 or less. If the molecular weight is 250 or more, volatilization from the vacuum vent during melt mixing and melt molding can be suppressed, and the release effect tends to be easier to achieve. Furthermore, during molding, sometimes suppressing wax seepage to a desired level can lead to mold contamination. On the other hand, if the molecular weight is 20,000 or less, there is a tendency for easy seepage, and the release effect tends to be improved.

[0091] As for this polyolefin-based wax (D), polyethylene wax and / or 1-olefin polymers polymerized from ethylene and / or 1-olefins are particularly preferred, as they not only provide excellent release properties but also result in superior adhesion between the PAS resin molded product and the coating. Methods widely known and commonly used in the present day can be used to manufacture the polyethylene wax, including: polymerization of ethylene under high temperature and pressure, thermal decomposition of polyethylene, and separation and purification of low molecular weight components from a polyethylene polymer. Examples of 1-olefins include propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, 1-heptadecene, 1-octadecene, 1-nonadecadecene, 1-eicosene, 1-docodecene, 1-docodidecene, 1-docotridecene, 1-dococosene, 1-docopentene, 1-docohexadecene, 1-dococapene, 1-dococapene, and 1-nonadecadecene. The aliphatic hydrocarbon groups constituting the polyolefin wax (D) used in this invention can be either linear or branched.

[0092] The polyolefin wax (D) used in this disclosure may also have polar groups. Examples of polar groups include at least one selected from the group consisting of carboxyl, acid anhydride, amino, hydroxyl, mercapto, epoxy, ether, ester, amide, imide, urea, urea and thioether bonds. When the polyolefin wax (D) used in this invention has polar groups, examples also include compounds that can copolymerize with the aforementioned monomers when polymerizing or copolymerizing the aforementioned ethylene and / or 1-olefins, having at least one selected from the group consisting of carboxyl, acid anhydride, amino, hydroxyl, mercapto, epoxy, ether, ester, amide, imide, urea, urea and thioether bonds, and having an olefinic double bond, preferably maleic anhydride or maleic anhydride and maleic acid.

[0093] The mixing ratio of the aforementioned polyolefin wax (D) is not particularly limited. From the perspective of further improving the adhesion to the coating obtained based on the aforementioned plating treatment, the ratio is preferably 0.01 parts by weight or more, more preferably 0.05 parts by weight or more, more preferably 0.1 parts by weight or more, more preferably 10 parts by weight or less, more preferably 5 parts by weight or less, and more preferably 2 parts by weight or less, relative to 100 parts by weight of the aforementioned PAS resin (A).

[0094] <Other arbitrary ingredients>

[0095] The PAS resin composition disclosed herein can be further blended with fillers other than carbonate (C) as any component. As the filler material, commonly known materials can be used as long as they do not impair the effects of the present invention; for example, filler materials of various shapes such as granular and fibrous materials can be used. Specifically, fibrous filler materials such as glass fiber, carbon fiber, silane glass fiber, ceramic fiber, aramid fiber, metal fiber, potassium titanate, silicon carbide, calcium sulfate, calcium silicate, and natural fibers such as wollastonite can be used. Additionally, barium sulfate, calcium sulfate, clay, pyrophyllite, bentonite, sericite, zeolite, mica, talc, attapulgite, ferrite, calcium silicate, and glass beads can be used. The filler used in this invention is not an essential component, but its mixing ratio is not particularly limited as long as it does not impair the effect of the invention. Furthermore, it varies depending on the intended purpose and cannot be uniformly limited. For example, relative to 100 parts by weight of the aforementioned PAS resin, it is preferably 10 parts by weight or more, more preferably 40 parts by weight or more, more preferably 90 parts by weight or less, and more preferably 70 parts by weight or less. Within this range, various properties such as strength, rigidity, heat resistance, heat dissipation, and dimensional stability can be improved depending on the purpose of the added filler.

[0096] The aforementioned filler material can also be one that has been processed with a surface treatment agent or a bridging agent. This improves the adhesion to PAS resin (A), and is therefore preferred. Examples of the aforementioned surface treatment agent or bridging agent include at least one polymer selected from the group consisting of silane compounds, titanate compounds, acrylic resins, polyurethane resins, and epoxy resins having functional groups such as amino, epoxy, isocyanate, and vinyl groups.

[0097] Furthermore, in the PAS resin composition disclosed herein, components other than the aforementioned thermoplastic resin (B) and the aforementioned polyolefin wax (D) can be appropriately blended into resins, such as epoxy resin, polyimide resin, polyetherimide resin, polyphenylene ether resin, polysulfone resin, polyethersulfone resin, polyetheretherketone resin, polyetherketone resin, polyaryl resin, polyethylene resin, polypropylene resin, polytetrafluoroethylene resin, polydifluoroethylene resin, polystyrene resin, ABS resin, phenolic resin, polyurethane resin, liquid crystal polymer, and other synthetic resins (hereinafter referred to as synthetic resins) as arbitrary components. The aforementioned synthetic resins in this invention are not essential components, but when blended, their blending ratio is not particularly limited as long as it does not impair the effect of this invention. Furthermore, it varies depending on the specific purpose and cannot be generalized. However, the ratio of synthetic resin blended in the resin composition of this invention can be, for example, in the range of 5 parts by mass or more and 15 parts by mass or less relative to 100 parts by mass of PAS resin (A). In other words, relative to the total amount of PAS resin (A) and synthetic resin, the proportion of PAS resin (A) by mass is preferably in the range of (100 / 115) or more, and more preferably in the range of (100 / 105) or more.

[0098] In addition, the PAS resin composition disclosed herein can be further formulated with commonly known additives such as colorants, antistatic agents, antioxidants, heat stabilizers, ultraviolet stabilizers, ultraviolet absorbers, foaming agents, flame retardants, flame retardant additives, rust inhibitors, and coupling agents as optional components, as needed. These additives are not mandatory components, but when formulated, their proportions are not particularly limited as long as they do not impair the effects of the present invention. Furthermore, they vary depending on the specific purpose and cannot be generalized. For example, the proportions are preferably 0.01 parts by weight or more and 1000 parts by weight or less relative to 100 parts by weight of PAS resin (A), and can be adjusted and used appropriately according to the purpose and application without impairing the effects of the present invention.

[0099] <Manufacturing Method of Electromagnetic Wave Shielding Components>

[0100] The electromagnetic wave shielding component disclosed herein is characterized in that it is formed from a laminate of a roughened surface of a molded article made of a PAS resin composition, on which a coating is laminated.

[0101] The plating of the aforementioned laminate consists of at least two paired surfaces.

[0102] The aforementioned PAS resin composition is made by compounding PAS resin (A), thermoplastic resin (B) other than PAS resin selected from the group consisting of thermoplastic elastomer (b1) and hydrolyzable thermoplastic resin (b2), carbonate (C) and olefin wax (D).

[0103] The PAS resin composition disclosed herein is prepared by using PAS resin (A), the aforementioned thermoplastic resin (B), the aforementioned carbonate (C), and the aforementioned polyolefin wax (D) as essential components, and blending any of the above components as needed. The method for manufacturing this PAS resin composition includes the following steps: using PAS resin (A), the aforementioned thermoplastic resin (B), the aforementioned carbonate (C), and the aforementioned polyolefin wax (D) as essential components, blending any of the above components as needed, and performing melt mixing at a temperature above the melting point of the PAS resin.

[0104] The preferred method for manufacturing the PAS resin composition disclosed herein can be achieved through the following steps: The aforementioned essential components and any of the aforementioned components, in various forms such as powder, granules, or flakes, are fed into a ribbon mixer, Henschel mixer, V-type agitator, etc., and dry-mixed. Then, the mixture is fed into a known melt mixer such as a Banbury internal mixer, roller mixer, single-screw extruder, twin-screw extruder, or kneader, and melt-mixed at a temperature above the melting point of the PAS resin, preferably above the melting point +10°C, more preferably between the melting point +10°C and the melting point +100°C, and even more preferably between the melting point +20°C and the melting point +50°C. The addition and mixing of each component in the melt mixer can be performed simultaneously or in batches.

[0105] From the viewpoint of dispersibility and productivity, a twin-screw compounding extruder is preferred as the aforementioned melt mixing mill. For example, it is preferable to perform melt mixing while appropriately adjusting the resin component discharge rate to a range of 5 to 500 kg / hr and the screw speed to a range of 50 to 500 rpm. More preferably, melt mixing is performed under conditions where their ratio (discharge rate / screw speed) is in the range of 0.02 to 5 kg / hr / rpm. Furthermore, when adding fillers or additives from the aforementioned components, from the viewpoint of dispersibility, it is preferable to feed them into the extruder through a side feeder of the aforementioned twin-screw compounding extruder. Regarding the location of the side feeder, the ratio of the distance from the extruder's resin input section (top feeder) to the side feeder to the total screw length of the aforementioned twin-screw compounding extruder is preferably 0.1 or more, more preferably 0.3 or more. Additionally, the ratio is preferably 0.9 or less, more preferably 0.7 or less.

[0106] The PAS resin composition of the present invention, obtained through such melt-blending, is a melt mixture comprising the aforementioned essential components, as well as any components added as needed and components derived therefrom. After melt-blending, the molten PAS resin composition is preferably extruded into a filament using a known method, for example, and then processed into granules, flakes, pellets, powders, etc., and pre-dried as needed within a temperature range of 100–150°C for various molding processes. When extruding into a filament, the following step may also be included: [The following step is also described:] [The resin composition of the present invention is subjected to a shear rate preferably 500 seconds...] -1 The following shearing region, more preferably a shearing speed of 100 seconds. -1 down to 0 seconds -1 Melting occurs within the shear zone described above.

[0107] The PAS resin composition of this disclosure, manufactured by the aforementioned manufacturing method, may contain, in addition to PAS resin (A), the aforementioned thermoplastic resin (B), the aforementioned carbonate (C), and the aforementioned polyolefin wax (D). It is believed that this PAS resin composition has a morphology in which at least one of the aforementioned thermoplastic resin (B) and the aforementioned carbonate (C) is formed in the continuous phase of the PAS resin. Furthermore, it is believed that by using the polyolefin wax (D), the effect of extruding the aforementioned thermoplastic resin (B) and the aforementioned carbonate (C) onto the surface of the molded article is improved. As a result, during the roughening process, the aforementioned thermoplastic resin (B) and the aforementioned carbonate formed on the roughened surface of the PAS resin molded article are removed, and the pores formed become easier to fill with metals, ceramics, etc., that constitute the coating through the plating process, further improving the adhesion between the coating and the molded article.

[0108] The PAS resin molded article constituting the electromagnetic wave shielding component of this disclosure is obtained, for example, by melt molding the aforementioned PAS resin composition. The manufacturing method of the PAS resin molded article of this invention includes a step of melt molding the aforementioned PAS resin composition. Alternatively, the manufacturing method of the PAS resin molded article of this invention may also include a step of melting the aforementioned PAS resin composition at a preferred shear rate of 500 seconds. -1 The following shearing region, more preferably a shearing speed of 100 seconds. -1 down to 0 seconds -1Melting occurs within the shearing region described above. Melt molding can be performed using known methods, such as injection molding, compression molding, blow molding, transfer molding, and other molding methods. In injection molding, there are no particular limitations on the molding conditions, and molding can be performed using common methods. For example, after melting the aforementioned PAS resin composition in an injection molding machine at a temperature above the melting point of the PAS resin, preferably above +10°C, more preferably between +10°C and +100°C, and even more preferably between +20°C and +50°C, the mixture can be injected into a mold from the resin outlet for molding. At this time, the mold temperature is preferably set to a known temperature range, for example, above room temperature (23°C), more preferably above 40°C, and even more preferably above 120°C. Furthermore, the mold temperature is preferably below 300°C, more preferably below 200°C, and even more preferably below 180°C.

[0109] The shape of the PAS resin molded articles disclosed herein is not particularly limited, and can be plate-shaped, box-shaped, cylindrical, hemispherical, etc. Furthermore, the shape of their bottom surface can be round, polygonal, or a combination of these shapes. The thickness of the PAS resin molded articles is preferably 0.5 mm or more, more preferably 1.0 mm or more, preferably 50 mm or less, and more preferably 10 mm or less. Additionally, in the case of a shape having a bottom and a wall, from a mechanical point of view, the thickness ratio (bottom / wall) is preferably in the range of 0.1 to 10. Furthermore, the connection between the bottom and the wall may also have an R (radius of curvature). Additionally, the PAS resin molded articles may also have ribs, hubs, pins, claws, etc. Furthermore, other components may be combined onto the surface of the PAS resin molded articles.

[0110] The laminate constituting the electromagnetic wave shielding member of this disclosure is manufactured by a manufacturing method comprising the following steps: a step of roughening the surface of the PAS resin molded article formed by the aforementioned PAS resin composition by chemical etching (hereinafter, sometimes simply referred to as the "roughening process"), and a step of plating the roughened surface of the aforementioned molded article (hereinafter, sometimes simply referred to as the "plating process").

[0111] Furthermore, the laminate constituting the electromagnetic wave shielding member of this disclosure has a coating on at least two paired surfaces of the PAS resin molded article. Therefore, compared to a laminate with a coating on only one surface, it can exhibit superior magnetic field shielding performance even with the same total coating thickness. Additionally, the total coating thickness can be reduced, thus reducing the amount of material used and consequently shortening the coating process time.

[0112] The aforementioned roughening process includes the following steps: applying an etching solution to the surface of the aforementioned PAS resin molded article by an immersion method and bringing it into contact with the surface.

[0113] The etching solution is not particularly limited as long as it can remove the aforementioned thermoplastic resin (B) and carbonate (C) present on the surface of the PAS resin molded article; for example, it preferably contains a strong acid or its salt. Examples of such strong acids or their salts include chromic acid, sulfuric acid, ammonium fluoride, nitric acid, and chromic anhydride, and one or more of them can be used. The conditions for contacting the surface of the aforementioned PAS resin molded article with the etching solution are preferably performed while appropriately adjusting the concentration of the strong acid or its salt in the etching solution, the temperature during contact, and the contact time.

[0114] The etching solution can use known substances. For example, the etching solution described in Japanese Patent Application Publication No. 5-155127, which contains 400 g / L sulfuric acid, 400 g / L chromic anhydride, and dilution water (total etching solution volume is set to 1 L), can be used.

[0115] Through the aforementioned roughening process, at least a portion of the aforementioned thermoplastic resin (B) and carbonate (C) uniformly dispersed on the surface of the PAS resin molded article are removed, forming pores. The presence of these pores and the increase in specific surface area further improve the interaction with the metal particles constituting the coating, thereby improving the adhesion between the PAS resin molded article and the coating. In addition, conventionally, when attempting to bond a coating formed by an adhesive or the like along the vertical direction of the molded article surface to the coating, the uncured adhesive or the like during manufacturing sags due to its own weight, causing film thickness deviations. Therefore, there is a tendency for uneven adhesion. However, in the present invention, there is a tendency for uneven pores to occur at locations on the surface of the molded article, thus the uniformity of adhesion is also excellent. The surface roughness of the roughened surface of the PAS resin molded article is not particularly limited, but from the viewpoint of excellent adhesion, it is preferably 0.1 μm or more, more preferably 1 μm or more to preferably 10 μm or less, and more preferably 5 μm or less, based on a ten-point average roughness Rz.

[0116] The plating process includes the following steps: forming a coating of metal and / or ceramic on the roughened surface of the aforementioned PAS resin molded article by means of chemical plating, electrolytic plating, sputtering or a combination thereof.

[0117] For chemical plating, the pores formed by removing the aforementioned thermoplastic resin (B) and the aforementioned carbonate on the roughened surface of the PAS resin molded article are easily filled with the metal or ceramic that constitutes the coating through the plating treatment, and the adhesion to the coating is further improved, so it is preferred.

[0118] The above-mentioned chemical plating method is as follows: the roughened surface of the aforementioned PAS resin molded article is brought into contact with the chemical plating solution, thereby causing the copper and other metals contained in the chemical plating solution to precipitate out, and a chemical plating layer (film) formed by the metal coating can be formed.

[0119] Examples of electroless plating solutions include those containing at least one metal selected from the group consisting of nickel, copper, chromium, zinc, iron, gold, silver, aluminum, tin, cobalt, palladium, lead, platinum, cadmium, manganese, lithium, strontium, lanthanum, titanium, barium, zirconium, lead, and rhodium, a reducing agent, an aqueous medium, and an organic solvent.

[0120] Examples of reducing agents mentioned above include dimethylaminoborane, hypophosphite, sodium hypophosphite, dimethylamineborane, hydrazine, formaldehyde, sodium borohydride, and phenol.

[0121] In addition, as the aforementioned chemical plating solution, complexing agents such as monocarboxylic acids (e.g., acetic acid, formic acid); dicarboxylic acid compounds (e.g., malonic acid, succinic acid, adipic acid, maleic acid, fumaric acid); hydroxycarboxylic acid compounds (e.g., malic acid, lactic acid, glycolic acid, gluconic acid, citric acid); amino acid compounds (e.g., glycine, alanine, iminodiacetic acid, arginine, aspartic acid, glutamic acid); amino polycarboxylic acid compounds (e.g., iminodiacetic acid, hypozinotriacetic acid, ethylenediaminediacetic acid, ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid) or soluble salts (sodium salts, potassium salts, ammonium salts, etc.) of these organic acids, as well as amine compounds (e.g., ethylenediamine, diethylenetriamine, triethylenetetraamine) can be used as required.

[0122] The aforementioned chemical plating solution is preferably used in the range of 20–98°C.

[0123] The aforementioned electroplating method is, for example, the following method: an electric current is applied to the surface of the chemical plating layer (film) formed by the aforementioned chemical plating treatment in contact with the electroplating solution, thereby causing the copper or other metal contained in the aforementioned electroplating solution to be deposited on the surface of the chemical plating layer (film) formed by the aforementioned chemical treatment and placed on the cathode, thus forming an electroplating layer (film).

[0124] Examples of electroplating solutions include sulfates containing at least one metal selected from the group consisting of nickel, copper, chromium, zinc, iron, gold, silver, aluminum, tin, cobalt, palladium, lead, platinum, cadmium, manganese, lithium, strontium, lanthanum, titanium, barium, zirconium, lead, and rhodium, along with an acid and an aqueous medium. Specifically, a permalloy coating is preferably obtained using a solution containing ferrous(II) sulfate, nickel(II) sulfate, boric acid, and an aqueous medium. The permalloy layer exhibits high magnetic permeability and good magnetic field shielding properties.

[0125] The aforementioned electroplating solution is preferably used in the range of 20–98°C.

[0126] The sputtering method is as follows: an inactive gas (mainly argon) is introduced into a vacuum, a positive discharge is applied to the aforementioned PAS resin molded article, and a negative discharge is applied to the metal material and ceramic material (target) to form the coating, generating a glow discharge. Then, the aforementioned inactive gas atoms are ionized and rapidly bombarded at high speed to the target surface, causing the atoms and molecules constituting the aforementioned target to be ejected and attached to the roughened surface of the aforementioned PAS resin molded article, thereby forming a coating.

[0127] Examples of sputtering methods include bipolar sputtering, magnetron sputtering, dual magnetron sputtering, reactive sputtering, and ion beam sputtering. These methods can be used individually or in combination of two or more. Furthermore, the target can be applied using any of the following methods: DC (direct current) sputtering, DC pulse sputtering, AC (alternating current) sputtering, and RF (high frequency) sputtering.

[0128] As a target for sputtering, examples include those containing at least one metal selected from the group consisting of nickel, copper, chromium, zinc, iron, gold, silver, aluminum, tin, cobalt, palladium, lead, platinum, cadmium, manganese, lithium, strontium, lanthanum, titanium, barium, zirconium, lead, and rhodium. Permalloy, iron-silicon-aluminum alloy, and ferrite are particularly preferred. When the coating contains permalloy, iron-silicon-aluminum alloy, and ferrite, it has high magnetic permeability and can exhibit good magnetic field shielding properties.

[0129] The thickness of the coating formed by the aforementioned plating process is not particularly limited, but is preferably in the range of 0.1 μm or more to 500 μm or less. The thickness of the coating formed by the aforementioned plating process can be adjusted according to the processing time, number of processing steps, current density, amount of plating additives, etc. in the plating process.

[0130] The laminate manufactured by the above-described manufacturing method can be used individually as an electromagnetic wave shielding component, or multiple laminates can be joined together for use. There are no particular limitations on the joining method; examples include mechanical joining methods such as threading, riveting, and snap-fit ​​assembly, methods using adhesives, and methods joining by welding.

[0131] The shape of the electromagnetic wave shielding member disclosed herein is not particularly limited as long as it surrounds the object to which electromagnetic waves are to be shielded, and can be box-shaped, cylindrical, hemispherical, etc. Furthermore, the shape of its bottom surface can be circular, polygonal, or a combination of these shapes. The thickness of the bottom and wall portions is preferably 0.5 mm or more, more preferably 1.0 mm or more, preferably 50 mm or less, and more preferably 10 mm or less. Furthermore, from a mechanical point of view, the ratio of the thickness of the bottom and wall portions (bottom / wall portion) is preferably in the range of 0.1 to 10. Additionally, the connection between the bottom and wall portions may have an R (radius of curvature). Furthermore, the bottom and wall portions may also have ribs, hubs, pins, claws, etc. Moreover, other components may be provided on the surfaces of the bottom and wall portions.

[0132] For the electromagnetic wave shielding component of this disclosure, a coating is formed by plating in the roughened surface of the PAS resin molded article, i.e., in the pores formed by removing the aforementioned thermoplastic resin (B) and the aforementioned carbonate (C). The thin film layer formed by metal or ceramic, i.e. the coating, is bonded to the PAS resin molded article with high adhesion.

[0133] The electromagnetic wave shielding component disclosed herein exhibits excellent electric and magnetic field shielding properties. Specifically, the electric field shielding at 1 GHz is greater than 100 dB, and the magnetic field shielding at 100 kHz is greater than 10 dB, as measured by the KEC method. It should be noted that the KEC method is a method developed by the Kansai Electronics Industry Promotion Center (KEC) and refers to the electromagnetic wave shielding characteristic measurement method in KEC.

[0134] Example

[0135] The present invention will now be described in detail with reference to embodiments, but the present invention is not limited to the embodiments described below. It should be noted that parts and percentages are used as mass standards unless otherwise specified.

[0136] (Manufacturing process of PAS resin composition and PAS resin molded articles)

[0137] According to the composition and mixing amount (all by weight) of the resin composition as described in Tables 1 and 2, all materials except glass fiber were uniformly mixed in a drum. Then, the aforementioned compounded materials were fed into the feed port (top feeder) of a twin-screw extruder (manufactured by Nippon Steel Corporation, "TEX30α") ​​with a vent, and glass fiber was fed into the side feeder. The resin component discharge rate was set to 30 kg / h, the screw speed was set to 220 rpm, and the resin temperature was set to 320°C. The mixture was melt-mixed, and the strands discharged from the discharge port were cut to obtain granules. Then, the above-mentioned granules were fed into an injection molding machine (manufactured by Sumitomo Heavy Industries, Ltd., “SE75D-HP”) with the barrel temperature set at 310°C, and injection molding was performed using a flat mold with the mold temperature set at 140°C to obtain each PAS resin molded product (150 mm in length, 150 mm in width, and 3 mm in thickness) of Examples 1 to 6, Reference Examples 1 to 5, and Comparative Examples 1 to 3.

[0138] [Example 1]

[0139] (Roughening process for PAS resin molded articles)

[0140] The PAS resin molded article obtained above is immersed in a chemical etching solution for 3 to 20 minutes, then removed, resulting in a roughened surface formed on the entire surface of the molded article. It should be noted that the chemical etching solution used contains 400 g / L sulfuric acid, 400 g / L chromic anhydride, and dilution water (total etching solution volume set to 1 liter).

[0141] (Plating process 1 for PAS resin molded articles)

[0142] Next, the roughened surface of the PAS resin molded article obtained above is subjected to electroless copper plating using the following method. The article is immersed in an electroless copper plating solution (manufactured by Okuno Pharmaceutical Co., Ltd., "OIC Cooper", pH 12.5) at 55°C for 100 minutes to form an electroless copper plating film (2.5 μm thick).

[0143] (Plating process for PAS resin molded articles 2)

[0144] Next, after thoroughly cleaning the surface of the electroless copper plating obtained above, it is immersed in an electroless nickel plating solution (manufactured by Okuno Pharmaceutical Co., Ltd., "TOP NICORON SA-98", pH9) at 30°C for 3 minutes to form an electroless nickel plating film (thickness 0.25μm).

[0145] [Example 2]

[0146] In the plating process of PAS resin molded articles (step 1), the thickness of the electroless copper plating is set from 2.5 μm to 1.0 μm, and otherwise it is carried out in the same manner as in Example 1.

[0147] [Example 3]

[0148] Instead of (plating process 2 for PAS resin molded articles), the following (plating process 3 for PAS resin molded articles) is performed, otherwise, it is performed in the same manner as in Example 2.

[0149] (Plating process for PAS resin molded parts, step 3)

[0150] The electroless copper plating surface obtained in the above (plating process 1 for PAS resin molded articles) is placed on the cathode, and nickel is placed on the anode. Electrolytic plating solution is used at a current density of 63 A / dm³. 2 Electroplating based on pulsed current was performed for 28 minutes at pH 2.7 and room temperature to deposit a 5 μm thick permalloy coating on the surface of the aforementioned electroless copper film. The pulsed current was as follows: the time during which the current flowed (ON time) and the time during which the current did not flow (OFF time) were combined as one cycle, and the cycle time was gradually shortened from ON time:OFF time = 2000 ms: 1000 ms to 2 ms: 1 ms. It should be noted that the aforementioned electroplating solution used was an aqueous solution containing 67 g / L nickel(II) hexahydrate, 133 g / L nickel(II) hexahydrate, 5 g / L ferrous(II) sulfate heptahydrate, 83 g / L boric acid, 83 g / L sodium chloride, 5 g / L sodium saccharin, and 0.3 g / L sodium lauryl sulfate.

[0151] [Example 4]

[0152] Instead of (plating process 2 for PAS resin molded articles), the following (plating process 4 for PAS resin molded articles) is used, except that it is performed in the same manner as in Example 2.

[0153] (Plating process for PAS resin molded parts, step 4)

[0154] A PAS resin molded part and an iron-silicon-aluminum alloy as a sputtering target are placed inside a vacuum chamber (manufactured by Toyoko Chemical Co., Ltd., SSP1000). Air is purged from the vacuum chamber, and argon gas is introduced to maintain the chamber at a sputtering gas pressure of 4 × 10⁻⁶. -1 After applying an argon atmosphere to the target, a sputtering power of 1 kW is applied to begin sputtering. Once the desired film thickness is achieved, the voltage application is released, and sputtering ends. Then, the PAS resin molded article is flipped over and placed in the chamber, and the other side is sputtered in the same manner.

[0155] [Example 5]

[0156] In the plating process of PAS resin molded articles (4), a ferrite target is used instead of an iron-silicon-aluminum alloy. Otherwise, the process is the same as in Example 4.

[0157] [Example 6]

[0158] The roughening and plating processes for the PAS resin molded articles were performed in the same manner as in Example 1.

[0159] [Reference Example 1]

[0160] A 3M coating masking tape (851A) is applied to a single side of the PAS resin molded article, measuring 150 mm in length and 150 mm in width, to cover the entire surface. Then, in (coating process 1 for the PAS resin molded article), the thickness of the electroless copper plating is changed to 5 μm, and in (coating process 2 for the PAS resin molded article), the thickness of the electroless nickel plating is changed to 0.5 μm. Otherwise, the process is the same as in Example 1. After the plating process, the coating masking tape is removed, resulting in an electromagnetic wave shielding member with a coating on only one of the two paired surfaces.

[0161] [Reference Example 2]

[0162] In the plating process (for PAS resin molded articles 1), the thickness of the electroless copper plating is set from 5 μm to 2 μm, and otherwise it is performed in the same manner as in Reference Example 1.

[0163] [Reference Example 3]

[0164] Instead of (plating process 2 for PAS resin molded articles), plating is performed by (plating process 3 for PAS resin molded articles), and the thickness of the electrolytic permalloy plating is set from 5 μm to 10 μm. Otherwise, it is performed in the same manner as in Reference Example 2.

[0165] [Reference Example 4]

[0166] Instead of (plating process 2 for PAS resin molded articles), plating is performed by (plating process 4 for PAS resin molded articles), and the thickness of the iron-silicon-aluminum alloy plating layer is set from 5 μm to 10 μm. Otherwise, it is performed in the same manner as in Reference Example 2.

[0167] [Reference Example 5]

[0168] In the plating process of PAS resin molded articles (4), ferrite is used instead of iron-silicon-aluminum alloy for the target used, otherwise the process is the same as in Reference Example 4.

[0169] [Comparative Example 1]

[0170] The same procedure as in Example 1 was performed. No coating was formed, resulting in an uncoated PAS resin molded article.

[0171] [Comparative Example 2]

[0172] The roughening and plating processes for the PAS resin molded articles were performed in the same manner as in Example 1.

[0173] [Comparative Example 3]

[0174] The same procedure as in Example 1 was performed. No coating was formed, resulting in an uncoated PAS resin molded article.

[0175] Using the above method, laminates with coatings formed on the PAS resin molded articles of Examples 1-6, Reference Examples 1-5, and Comparative Examples 1-3 were obtained. The obtained laminates were evaluated as follows.

[0176] <Evaluation>

[0177] (1) Determination of coating adhesion (bonding)

[0178] A cross-cut test was performed using the adhesive tape specified in JIS Z 1522 (adhesive strength: approximately 8 N relative to a 25 mm width, nominal width: 12–19 mm, manufactured by NICHIBAN Co., Ltd., Cellotape (registered trademark) No. 405). Specifically, the following steps were followed: First, on the plated surface obtained by creating 3×6=18 squares (2 mm sides) with a sharp blade to form a grid reaching the workpiece, 30–50 mm of the tape remained unadheded to the workpiece at one end. The center of the tape was placed on the grid, and the tape was flattened by pressing it with a finger. At this point, while being careful not to create air bubbles, a cross-cut test was performed at 20 N / cm. 2 Press firmly and continuously for approximately 10 seconds. Within 1 minute, hold the unadhesive, residual portion of the tape and peel it off at a speed of 200 cm / s at a 90° angle relative to the coated surface. For samples with coating on both sides of a pair, evaluate both sides and use the one with the worse result. In the table, "0 / 18" means 0 meshes were peeled off, and "18 / 18" means 18 meshes were peeled off. It should be noted that the fewer peeled surfaces within 18 meshes, the stronger the adhesion is considered. The evaluation results are shown in Tables 1 and 2.

[0179] (2) Evaluation of electric field shielding and magnetic field shielding

[0180] The electric field shielding and magnetic field shielding properties of each laminate fabricated in Examples 1-6, Reference Examples 1-5, and Comparative Examples 1-3 were determined by the KEC method. The evaluation results of the electric field shielding [dB] at a frequency of 1 GHz and the magnetic field shielding [dB] at a frequency of 100 kHz are shown in Tables 1 and 2.

[0181] [Table 1]

[0182]

[0183] [Table 2]

[0184]

[0185] <Raw Materials Used>

[0186] The following shows the raw materials and components of the coating that make up the PAS resin composition.

[0187] PAS resin

[0188] (A) Melt viscosity of linear polyphenylene sulfide resin (V6) 8 Pa·s

[0189] • Thermoplastic resins (thermoplastic elastomers) other than PAS resin

[0190] (b1-1) Olefin polymer “Bondfast 7L” (ethylene-maleic anhydride-glycidyl methacrylate copolymer), manufactured by Sumitomo Chemical Co., Ltd.

[0191] (b1-2) Olefin polymer "ENGAGE 8842" (ethylene-α-olefin polymer), manufactured by Dow Chemical Company

[0192] • Thermoplastic resins other than PAS resin (hydrolyzable thermoplastic resins)

[0193] (b2-1) Polyamide resin "AMODEL A-1004", manufactured by Amomantec Co., Ltd.

[0194] (b2-2) Polycarbonate resin "Lupilon MB4304R", manufactured by Mitsubishi Chemical Corporation

[0195] Carbonates

[0196] (C-1) Calcium carbonate "Calcium carbonate NS#2300" (average particle size) ※3 1.0μm), manufactured by Nitto Powder Chemical Co., Ltd.

[0197] (C-2) Calcium carbonate "Grade 1 calcium carbonate" (average particle size) ※3 6.4μm), manufactured by Sankyo Milling Co., Ltd.

[0198] (C-3) Magnesium carbonate (synthetic magnesite) "Magnesium MS-S" (average particle size) ※3 1.2μm), manufactured by Kamishima Chemical Industry Co., Ltd.

[0199] Average particle size ※3 The average particle size of the powder is calculated using the formula (average particle size = 6 / (specific gravity × specific surface area) × 10000 [μm]) based on the specific surface area value of 1g of powder manufactured by Shimadzu Corporation, based on the powder specific surface area measuring device "SS-100".

[0200] ·wax

[0201] (D-1) High-density polyethylene wax "Luwax AH-6" manufactured by BASF Corporation

[0202] (D-2) Maleic anhydride polyethylene "Licolub CE-2" manufactured by Clariant Japan Co., Ltd.

[0203] (d-3) Pentaerythritol fatty acid ester "Loxiol VPG861" manufactured by Green Polymer Additives

[0204] ·other

[0205] (E) Glass fiber "T-717H" (fiber length 3mm, average diameter 10μm), manufactured by Nippon Electric Glass Co., Ltd.

[0206] • Composition of the coating

[0207] (G-1) Copper

[0208] (G-2) Nickel

[0209] (G-3) Permalloy (Fe-Ni alloy, nickel content 70-85%)

[0210] (G-4) Iron-silicon-aluminum alloy (Fe-Si-Al alloy, Si content 9.5-10.5%, Al content 4.5-5.5%)

[0211] (G-5) Ferrite (Fe2O3-MnO-ZnO ceramic, MnO content 33-40%, ZnO content 6-13%)

Claims

1. A method for manufacturing an electromagnetic wave shielding component, characterized in that, This is a method for manufacturing an electromagnetic wave shielding component formed by a laminate, the method comprising the following steps: a step of roughening the surface of a molded article formed from a polyarylene sulfide resin composition by chemical etching, and a step of plating the roughened surface of the molded article. The laminate has a coating on at least two paired surfaces. The polyarylene sulfide resin composition is made by blending polyarylene sulfide resin (A), a thermoplastic resin (B) selected from the group consisting of thermoplastic elastomer (b1) and hydrolyzable thermoplastic resin (b2) excluding polyarylene sulfide resin, a carbonate (C), and a polyolefin wax (D). The hydrolyzable thermoplastic resin (b2) is a polyamide resin. The carbonate (C) is a granular material with an average particle size ranging from 0.3 μm to 6 μm.

2. The method for manufacturing the electromagnetic wave shielding component according to claim 1, wherein, The process of roughening the surface of a molded article formed from a polyarylether sulfide resin composition by chemical etching is a process of contacting the surface of the molded article with an etching solution containing a strong acid or its salt.

3. The method for manufacturing the electromagnetic wave shielding component according to claim 1 or 2, wherein, The carbonate (C) is selected from at least one of the following groups: calcium carbonate, magnesium carbonate, potassium carbonate, sodium carbonate, sodium bicarbonate, ammonium carbonate, barium carbonate, lithium carbonate, copper carbonate (II), ferrous carbonate (II), silver carbonate (I), manganese carbonate, zinc carbonate, dolomite, and hydromagnesite.

4. The method for manufacturing the electromagnetic wave shielding component according to claim 1 or 2, wherein, It also contains fibrous fillers.

5. The method for manufacturing the electromagnetic wave shielding component according to claim 1 or 2, wherein, Plating processes include chemical plating, electrolytic plating, sputtering, and combinations thereof.

6. The method for manufacturing the electromagnetic wave shielding component according to claim 1 or 2, wherein, The components constituting the coating include at least one metal from the group consisting of nickel, copper, chromium, zinc, iron, gold, silver, aluminum, tin, cobalt, palladium, lead, platinum, cadmium, manganese, lithium, strontium, lanthanum, titanium, barium, zirconium, lead and rhodium.

7. The method for manufacturing an electromagnetic wave shielding component according to claim 1 or 2, wherein, The components constituting the coating include at least one of the group consisting of permalloy, iron-silicon-aluminum alloy and ferrite.

8. An electromagnetic wave shielding component, characterized in that, It is formed by laminating a coating onto the roughened surface of a molded article made of a polyarylether sulfide resin composition. The laminate has a coating on at least two paired surfaces. The polyarylene sulfide resin composition is made by blending polyarylene sulfide resin (A), a thermoplastic resin (B) selected from the group consisting of thermoplastic elastomer (b1) and hydrolyzable thermoplastic resin (b2) excluding polyarylene sulfide resin, a carbonate (C), and a polyolefin wax (D). The hydrolyzable thermoplastic resin (b2) is a polyamide resin. The carbonate (C) is a granular material with an average particle size ranging from 0.3 μm to 6 μm.

9. The electromagnetic wave shielding component according to claim 8, wherein, The carbonate is selected from at least one of the following groups: calcium carbonate, magnesium carbonate, potassium carbonate, sodium carbonate, sodium bicarbonate, ammonium carbonate, barium carbonate, lithium carbonate, copper (II) carbonate, ferrous (II) carbonate, silver (I) carbonate, manganese carbonate, zinc carbonate, dolomite, and hydromagnesite.

10. The electromagnetic wave shielding member according to claim 8 or 9, wherein, It also contains fibrous fillers.

11. The electromagnetic wave shielding member according to claim 8 or 9, wherein, The components constituting the coating include at least one metal from the group consisting of nickel, copper, chromium, zinc, iron, gold, silver, aluminum, tin, cobalt, palladium, lead, platinum, cadmium, and rhodium.

Citation Information

Patent Citations

  • Metal plating treatment

    JP1988014880A

  • JP1988055008A

  • Light-transmitting type display member and manufacture thereof

    JP1993155127A

  • Method of forming coating on crystalline thermoplastic resin molding

    JP2002097292A

  • Method for manufacturing laminate

    WO2017154879A1